Enhancing Micro, Small, and Medium Enterprises' Promotional Capacity through Canva-Based Digital Content Design Training: A Visual Branding Consistency and Post-Training Engagement Approach in Kota Banjar, West Java, Indonesia - Setyo Luthfi Okta Yohandoko; Nestia Lianingsih; Kiki Zakaria (Research Collaboration Community (Rescollacom), 2026)
Micro, Small, and Medium Enterprises (MSMEs), locally known as UMKM, contribute more than 61% of Indonesia's Gross Domestic Product and absorb approximately 97% of the national workforce (Kementerian Koperasi dan Usaha Kecil dan Menengah Republik Indonesia, 2024; Kementerian UMKM Republik Indonesia, 2025), yet a large proportion of business owners still struggle to produce professional promotional content because of limited digital design skills, time, and budget. This community service program addressed that gap by delivering a structured Canva-based digital content design training to 30 MSME actors in Kelurahan Hegarsari, Kecamatan Pataruman, Kota Banjar, West Java. Unlike most previous Canva-training community service reports, which generally evaluate outcomes through a single pretest-posttest knowledge score, this program introduced two additional evaluation instruments: a five-indicator Visual Branding Consistency (VBC) rubric to assess the strategic quality of participants' design outputs, and a four-week post-training monitoring phase tracking participants' actual social media posting frequency and engagement performance. The training was designed using the ADDIE instructional model (Analysis, Design, Development, Implementation, Evaluation) and interpreted through Diffusion of Innovation theory (Rogers, 2003) and the Technology Acceptance Model (Davis, 1989). Results showed a statistically significant increase in mean knowledge score from pretest (52.4) to posttest (81.7), t(29) = 14.62, p < .001; an average Visual Branding Consistency score of 78.3 out of 100; and, during the four-week follow-up, a 143% increase in weekly content-posting frequency together with a rise in the average engagement rate from 1.6% to 4.9%. These findings indicate that combining hands-on Canva training with a structured branding-consistency assessment and short-term post-training assistance produces more durable digital-marketing capacity among MSME actors than a single training session evaluated only through immediate knowledge gain. The program offers a replicable, low-cost model that other community service teams and local governments can adapt to accelerate MSME digitalization in similar semi-urban districts of Indonesia.